Water Absorption And Hygrothermal Aging Behavior Of Kenaf Fiber-Reinforced Poly(Lactic Acid) Composites - Thian, Yoke Teng (Universiti Sains Malaysia, 2022)
In the present study, the water absorption behaviour, mechanical, thermal and morphological properties of poly(lactic acid)/kenaf (PLA/KF) composites with different fiber size were investigated. PLA/KF composites were prepared by using single screw extruder and injection moulding method and followed by hygrothermal aging at 60 °C for 4 weeks. The water absorption and mechanical properties of the PLA/KF composites with immersion time were reported and compared to those of neat PLA. PLA/KF composites showed higher water uptake at equilibrium and diffusion coefficients than that of neat PLA, which indicated that the addition of kenaf fiber induced higher water absorption caused by the hydrophilic nature of the fibers. Tensile strength and tensile modulus severely decreased after aging. PLA/KF composite with larger fiber has higher tensile strength and modulus than that with smaller fiber due to its higher aspect ratio. The morphologies of surfaces and fractured surfaces of neat PLA and PLA/KF composites with different immersion time were observed by scanning electronic microscopy. The voids and micro-cracks were found which was due to the degradation of PLA and debonding of PLA and kenaf. FTIR spectrum showed that the number of –OH groups in PLA/KF composite after aging were more than composite before aging due to diffusion of water molecules into the composites. Tg and Tm for PLA/KF composites decrease after aging due to the reduction in molecular weight and plasticization effect of PLA were analysed by differential scanning calorimetry.